Persaksian Non-Muslim dalam Tinjauan Fikih Peradilan - Nur Shaliha; Rosmita Rosmita; Zulfiah Sam (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This research aims to determine the position of non-Muslims as witnesses in judicial jurisprudence reviews, as well as the validity of non-Muslim testimony in judicial jurisprudence reviews. This research uses library research, which focuses on the study of manuscripts and texts, using a normative approach and a conceptual approach. The results of the research are as follows: first, the position of non-Muslims as witnesses in judicial jurisprudence, namely, the jurists are of the opinion that non-Muslim witnesses cannot be used as witnesses because the witnesses are not people who meet the requirements. The reason the jurists do not justify the presence of non-Muslim witnesses is because of religious differences and a non-Muslim is not a just person and is often characterized as wicked. Non-Muslims are also considered not to be from groups that are pleased with Muslims. Meanwhile, according to Islamic law, the testimony of non-Muslims cannot be used as a witness because testimony is a matter of power, whereas non-Muslims are not people who have power over Muslims. However, due to differences of opinion among the ulama regarding the testimony of non-Muslims, there are a minority of ulama who accept the testimony of non-Muslims on the grounds of emergency, namely making a will while traveling. Second, the validity of non-Muslim testimony in judicial jurisprudence, namely Imam Syafi'i and Imam Malik are of the opinion that non-Muslims cannot be witnesses against Muslims and their testimony is not accepted absolutely. Meanwhile, Imam Hanafi and Imam Ibn Hanbal allow the testimony of non-Muslims against Muslims in testamentary cases while on pilgrimage. Ibnu Qayyim al-Jauziyah stated that the rejection of non-Muslim witnesses must be reviewed in the era of globalization where currently people live together, non-Muslim testimony can be accepted in emergency matters that are desired, both in travel and residence situations.